1994
DOI: 10.1038/bjc.1994.261
|View full text |Cite
|
Sign up to set email alerts
|

Role of reproductive factors in breast cancer in a low-risk area: a case–control study

Abstract: S_ary A case-control study of 689 breast cancer patients seen at Tata Memorial Hospital during the period 1980-84 was carried out. During the same period 711 females who attended the hospital without a history of benign breast lesions or gynaecological complaints were selected as controls. Patients were interviewed by trained investigators to collect data on reproductive factors, menstrual history, tobacco smoking and chewing habit, dietary practices (vegetarian and non-vegetarian diet) and alcohol consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 8 publications
4
61
0
3
Order By: Relevance
“…This finding is consistent with results from a hospital-based case-control study carried out in Bombay (India). 25 It is also consistent with findings from large follow-up studies of Western vegetarians and religious groups who tend to abstain from meat. 26 -30 In these studies, however, most subjects cease meat consumption in adult life and therefore it was not possible to exclude the possibility that meat intake might play a role in the causation of breast cancer if pre-adult life is a more critical period.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with results from a hospital-based case-control study carried out in Bombay (India). 25 It is also consistent with findings from large follow-up studies of Western vegetarians and religious groups who tend to abstain from meat. 26 -30 In these studies, however, most subjects cease meat consumption in adult life and therefore it was not possible to exclude the possibility that meat intake might play a role in the causation of breast cancer if pre-adult life is a more critical period.…”
Section: Discussionsupporting
confidence: 84%
“…In similar studies, the risk of BC was higher for unmarried women compared with married women (Gajalakshmi and Shanta, 1991;Rao et al, 1994;Pakseresht et al, 2009). Being single in Pakistani society is :http://dx.doi.org/10.7314/APJCP.2013.14.1.183 A Multicenter Matched Case Control Study of Breast Cancer Risk Factors among Women in Karachi, Pakistan reported to be psychosocially stressful.…”
Section: Discussionmentioning
confidence: 79%
“…Case-control studies in Mumbai and Chennai have identified the usual risk factors of nulliparity, early menarche, late age at marriage and late age at first pregnancy as important risk factors. 29,30 Incidence is much higher in urban than in rural women. 6 -8,10,23 This urban/rural difference could be due to differences in lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%